2016
DOI: 10.1016/j.matdes.2016.06.095
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of grain refinement of aluminium alloy in shear spinning under different deviation ratios

Abstract: To investigate the grain refinement and its mechanism in shear spinning, microstructures of shear spun parts made by aluminium alloy under different deformation conditions, induced by different shear spinning deviation ratios, are studied. The results show that, after shear spinning, the microstructure is distributed symmetrically about a zone in sheet thickness defined as the neutral zone which is located between the inner surface and the middle plane of spun sheet thickness.Various deviation ratios in shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The main strengthening alloy elements are Zn and Mg. The precipitation sequence of the alloy during aging treatment is: supersaturated solid solution (SSS) → solutevacancy → GP zone→ intermediate phase η′ or T′ → equilibrium phase η(MgZn2) or T(Mg32(Al, Zn)49) [8,9]. η′ is semi-coherent with the Al matrix, which is the main strengthening phase, and η is with the Al matrix, which results in a significant reduction in its strengthening effect [10].…”
Section: Figure 5 Positions Of Micro Hardness Measurement and Microstructure Observationmentioning
confidence: 99%
“…The main strengthening alloy elements are Zn and Mg. The precipitation sequence of the alloy during aging treatment is: supersaturated solid solution (SSS) → solutevacancy → GP zone→ intermediate phase η′ or T′ → equilibrium phase η(MgZn2) or T(Mg32(Al, Zn)49) [8,9]. η′ is semi-coherent with the Al matrix, which is the main strengthening phase, and η is with the Al matrix, which results in a significant reduction in its strengthening effect [10].…”
Section: Figure 5 Positions Of Micro Hardness Measurement and Microstructure Observationmentioning
confidence: 99%
“…Результаты исследования изменения микроструктуры при различных режимах деформирования в процессе формовки листовых изделий обкаткой роликами представлены в [Zhan et al, 2016]. Эксперименты проведены на образцах из алюминиевого сплава 3A21, заготовкакруглый в плане лист диаметром 290 мм и толщиной 6 мм, получаемая детальусеченный конус.…”
Section: методы и результаты экспериментальных исследований полученияunclassified
“…It can be found that the tensile strengths after deformation are all greater than the initial blank for all different zones and directions. Zhan et al [25] have reported that significant work hardening and grain refinement will produce in the power spinning of aluminum alloy. Thus, the tensile strength is improved during power spinning.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 99%